DO INFLATION AND EXCHANGE RATES MATTER FOR ISLAMIC AND CONVENTIONAL STOCK INDICES? EVIDENCE FROM INDONESIA - Ajuna, Luqmanul Hakiem (UIN Sunan Gunung Djati Bandung, 2025)
Stock Index (ISSI) and the Indonesia Composite Stock Price Index (IHSG). Employing a quantitative approach, the study utilizes monthly secondary data from 2014 to 2023 obtained from the Indonesia Stock Exchange, Bank Indonesia, and the Central Bureau of Statistics. Multiple linear regression analysis is applied to assess both partial and simultaneous effects of macroeconomic variables on Islamic and conventional stock market indices. The empirical results reveal that inflation does not have a significant effect on either ISSI or IHSG. In contrast, the rupiah exchange rate exerts a significant influence on both indices, indicating that exchange rate movements play a more dominant role in shaping stock market performance than inflation. These findings suggest that, within the Indonesian context, exchange rate dynamics constitute a key source of systematic risk affecting both Islamic and conventional equity markets. The results provide empirical support for the Arbitrage Pricing Theory by highlighting the unequal influence of macroeconomic factors on asset prices. This study contributes to the literature by offering comparative evidence on the sensitivity of Islamic and conventional stock markets to macroeconomic conditions in an emerging economy.